Emotional Agency - Koszegi, B. (Quarterly Journal of Economics, 2006)
This paper models interactions between a party with anticipatory emotions and a party who responds strategically to those emotions, a situation that is common in many health, political, employment, and personal settings. An “agent” has information with both decision-making value and emotional implications for an uninformed “principal” whose utility she wants to maximize. If she cannot directly reveal her information, to increase the principal's anticipatory utility she distorts instrumental decisions toward the action associated with good news. But because anticipatory utility derives from beliefs about instrumental outcomes, undistorted actions would yield higher ex ante total and anticipatory utility. If the agent can certifiably convey her information, she does so for good news, but unless this leads the principal to make a very costly mistake, to shelter his feelings she pretends to be uninformed when the news is bad.